Evaluación del desempeño de las variables del comportamiento organizacional a nivel grupal en empresa comercializadora de productos cárnicos del cantón Portoviejo - Solórzano Vera, María Margoth (2016)
The present research propose an improvement plan for labour climate in the meat trading company Fresh Fish in Portoviejo Canton, based in the analysis and management of labour satisfaction; using different information methods like the inductive, deductive, bibliographic among others there were a great help to obtain information on the subject. Tools like interview and survey allowed to study onsite and gather suitable data of the members in the company, the questionnaire was conformed by 20 questions headed to the workers and the interview with ten questions directed to the manager, the information was input in Excel 2013, and made presentation with pictures and statistical charts that allowed to appreciate better, analyzing the most notable variables of the company. The contributions of this investigation gave a measurement for the Organizational Behavior, the work provided a distinct vision regarded to the perception of the collaborators showing low indicators like motivation and team work, the results of study facilitated the management directed for the improvement in the business labour field with vision and approach on efficiency and team work.